2020
DOI: 10.1016/j.eclinm.2020.100490
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic value of Delirium as the initial presentation of COVID-19 in the elderly with dementia: An Italian retrospective study

Abstract: Background Delirium may be one of the presenting symptoms of COVID-19, complicating diagnosis and care of elderly patients with dementia. We aim to identify the prevalence and prognostic significance of delirium as the sole onset manifestation of COVID-19. Methods This is a retrospective single-centre study based on review of medical charts, conducted during the outbreak peak (March 27-April 18, 2020) in a Lombard dementia facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 31 publications
7
96
4
3
Order By: Relevance
“…Although delirium onset does not appear to be related to gender, it is more frequent with older age, and male gender is an independent risk factor for poor outcome, including mortality [65]. Having said that, case reports also draw the attention to COVID-19 positive older people asymptomatic or with non-specific clinical features, who develop delirium as first clinical symptoms of the viral infection [66,67] and in some instances related to leukoencephalopathy, as seen on CT brain scans [68].…”
Section: Delirium In Covid-19mentioning
confidence: 84%
“…Although delirium onset does not appear to be related to gender, it is more frequent with older age, and male gender is an independent risk factor for poor outcome, including mortality [65]. Having said that, case reports also draw the attention to COVID-19 positive older people asymptomatic or with non-specific clinical features, who develop delirium as first clinical symptoms of the viral infection [66,67] and in some instances related to leukoencephalopathy, as seen on CT brain scans [68].…”
Section: Delirium In Covid-19mentioning
confidence: 84%
“…According to recent studies, and in line with our findings, delirium has been described as a clinical manifestation in older patients with COVID-19. 11 , 24 In this regard, we did not evaluate the other items of the Confusion Assessment Method (ie, acute and fluctuating course, inattention, or disorganized thinking); however, we suspect that the incidence of delirium was high due to the large number of patients presenting altered level of consciousness and the prevalence of dementia in our sample. These data also reveal the importance of identifying atypical presentations of this disease in the older population.…”
Section: Discussionmentioning
confidence: 98%
“… Bianchetti et al (2020) found that the most frequent symptom of onset was delirium (67%) among dementia patients diagnosed with COVID-19. Similarly, Poloni et al (2020) emphasized that delirium may be representative of an early-phase clinical feature of COVID-19, especially in elderly patients. In this context, it becomes clear that clinicians should be alert of the fact that delirium may develop, especially in the first days of hospitalization.…”
Section: Discussionmentioning
confidence: 99%